Actuating Soft-Skills through E-Learning in Higher Education: Addressing the Importance of Soft Skills and Entrepreneurship in Higher Education (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Higher education and skill development play a vital in the development of an individual as well as the whole society. Presently, education is closely connected with employability where soft skills are regarded as pre-requisites. Soft skills refer to a cluster of personal qualities, habits, attitudes that contribute to become an employable and a successful professional. Good communication skills are indispensable asset of a profession. Listening, Speaking, Writing and Reading skills (LSWR) are undoubtedly regarded as cornerstone of success in a profession and also determiners of a person’s competency to fit into a particular ambience that is another objective of Higher education in the modern times. According to Daneil Goleman, soft skills contribute to a person’s ability to manage himself or herself and relate to other people. These skills matter twice as much as Intelligent Quotient(IQ) or technical skills in employ ability.Excellence in education demands the education of necessary skills in order to make the masses self-sufficient, employable or entrepreneurs. It is time for teachers, trainers and stakeholders to incorporate soft skills in their education and its practice because imparting soft skills would preferably aim at the individual’s competencies not only to collect and transform knowledge. It also reflects on the complexity and interrelations of behaviour as well as decision-making in a futuristic and global perspective.The present paper focuses on the issues and concerns related to soft skills and entrepreneurship in higher education.